Nicomachean Ethics VI.9: good deliberation and phronesis [Ética a Nicômaco VI.9: boa deliberação e phronesis] - Angelo Antonio Pires de Oliveira (Princípios, 2017)
In this paper, I put under scrutiny the arguments put forward by Aristotle in Nicomachean Ethics (NE) VI.9. The paper has two main parts. In the first, I examine the NE VI.9’s first part where Aristotle develops the concept of good deliberation, offering its definition in 1142b27-28. In the second, I examine the connection between good deliberation and phronesis, and, then, discuss the vexata quæstio about if the lines 1142b31-33 might be read as introducing the claim that phronesis provides moral ends.